(untitled) (SCHOLARS: Journal of Arts & Humanities, 2019)
This paper explores and recognizes common points of intersection of law and literature. Different literary texts have legal language, court scenes, cross examinations, lawyers, witnesses, judge, and audience. The main focus of this paper is to identify such events from literary texts and also to present instances that people take into the courts from literary texts. Law and literature originate and develop, after all, from the same culture and society. Humanities and social sciences are common grounds of origin and development of law and literature. They are related with each other. They do have correlation on the basis of culture, social norms and values, and humanities. In this paper, they discussed on the grounds of cognitive and behaviouristic aspects of human life.